Diagnosing Urogenital Schistosomiasis: Dealing with Diminishing Returns. Issue 5 (May 2017) - Le, Loc; Hsieh, Michael H.
Abstract : Urogenital schistosomiasis, caused by Schistosoma haematobium, is the most prevalent form of schistosomiasis affecting humans, and can result in severe bladder, kidney, ureteral, and genital pathologies. Chronic infection with S. haematobium has been linked with bladder cancer and increased risk for HIV infection. As mass drug administration with praziquantel increases in an attempt to transition from control to elimination of schistosomiasis, the need for updated, more sensitive diagnostic tools becomes more apparent, especially for use in areas of low infection intensity and for individuals with light infections. Here, we review established and investigational diagnostic tests utilized for urogenital schistosomiasis, highlighting new insights and recent advances. Trends: The current standard-of-care diagnostic for urogenital schistosomiasis is syringe filtration of urine and counting eggs retained on the filter. Syringe filtration is labor-intensive, requires a microscope, and can miss light infections. Ongoing research is developing alternatives to syringe filtration, including questionnaires, urine reagent strip tests, antibody-based detection of circulating cathodic antigen (CCA), circulating anodic antigen (CAA), and other analytes, PCR/DNA-based methods (including electrochemical biosensors and loop-mediated isothermal amplification), mobile microscopy, and microfiltration technology. Diagnosis of female genital schistosomiasis remains a challenge due to ethical and cultural barriers to colposcopy and biopsy of the female genital tract.